INFLUENCE OF MANAGEMENT STYLES ON SUSTAINABLE PERFORMANCE CONTRACTING OF EMPLOYEES IN CHARTERED PUBLIC UNIVERSITIES IN KENYA - Amwayi, Joshua Enane; Iravo, Prof. Mike Amuhaya; Odhiambo, Prof. Romanus; Lutsili, Dr. Victor Ladan (European Journal of Business and Strategic Management, 2018)
Purpose: The purpose of the study was to determine the influence of management styles on sustainable performance contracting of employees in chartered public universities in Kenya Methods: The study adopted a descriptive research design. This study adopted a positivist research philosophy. The population of the study comprised of all the staff members in public chartered universities in Kenya. For this study, target population was 27,054. This figure comprised of various staff at the universities who included; the Academic, Administrative and Technical staff. Various strata were identified from the areas of academic specialization of schools or faculties. The sample size was 384 respondents. Primary data was collected by use of one main structured questionnaire that captured the various variables of the study. Both descriptive and inferential statistics were used. Results: The study concluded that there existed a significant positive relationship between management styles and sustainable performance contracting of employees in chartered public universities in Kenya. Unique contribution to theory, practice and policy: The study recommends adoption of management styles that are characterized by attributes such as focus on improvement of employee productivity, commitment to enhancement of employees' skills and competencies, fair treatment of all employees, close collaborations' and open communication with the staff and participative leadership where the employees are allowed to offer input in crucial organizational matters. Keywords: Management styles, sustainable performance contracting, employees, chartered public universities